ESG AND CAPITAL STRUCTURE: A HYBRID SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Lailiyah, Elliv Hidayatul; Abdullah, Ahmad Ridhuwan; Mohd Din, Noormariana (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
In recent years, numerous studies have examined the role of ESG in financing decisions. However, comprehensive and systematic studies that map research developments, thematic focus, theoretical and practical implications regarding the relationship between ESG and capital structure are still relatively limited. Existing literature still shows inconsistent empirical findings regarding the influence of ESG on corporate leverage decisions. Furthermore, there are few studies that systematically map the intellectual structure, publication trends, and future research directions in the ESG and capital structure literature through systematic literature reviews and bibliometric analysis. This study aims to conduct a Systematic Literature Review (SLR) and bibliometric analysis of empirical studies discussing ESG and capital structure. This study uses the SLR method by searching for keywords related to ESG and capital structure of articles indexed in the Scopus database. The final sample consists of publications of 2012–2025 and are evaluated at the end of 2025. Data are analyzed using a bibliometric approach with VOSviewer to identify publication trends, author collaborations, and thematic research clusters. The analysis results indicate that research on ESG and capital structure has experienced significant growth in recent years, with a primary focus on the effect of ESG on leverage, the cost of capital, and access to financing. Previous studies have been dominated by developed countries, while research in emerging economies is increasing but remains limited. This research contributes by mapping research clusters, publication trends, and inter-topic relationships in the ESG and capital structure literature through bibliometric analysis. Furthermore, it identifies inconsistencies in empirical findings and existing theoretical gaps, and proposes a future research agenda to develop a more integrated study of ESG and capital structure.